Islamic financial development, institutional environment and economic growth - Ahlem, Boubaker; Mrad, Fatma; Hadhek, Zouhaier; Telmoudi, Fedya (Technium Social Sciences Journal, 2021)
The emergence of Islamic finance in recent years, and its increasingly important role in the financial industry, has made us real investigators in studying the nature of the relationship that can be established between the development of Islamic finance and economic growth. To this end, we opted for an empirical validation test based on a dynamic panel data model.Our sample consists of 25 Islamic banks from seven countries observed during the period 2007-20014 ; with the data being annual. Our results indicate that:a positive effect of Islamic finance on economic growth, a positive interaction between Islamic finance, government efficiency, rule of law, and regulatory quality. However, we found a negative interaction between Islamic finance, corruption, political stability and Voice and Accountability.